Post-configuration Activation of Hardware Trojans in FPGAs - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (Journal of Hardware and Systems Security)
Keywords: General Engineering; Energy Engineering and Power Technology

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Three-dimensional dipole momentum analog based on L-shape metasurface - Li, Tianyou; Chen, Yanjie; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Applied Physics Letters)
The achievement of a flat metasurface has realized extraordinary control over light–matter interaction at the nanoscale, enabling widespread use in imaging, holography, and biophotonics. However, three-dimensional metasurfaces with the potential to provide additional light–matter manipulation flexibility attract only little interest. Here, we demonstrate a three-dimensional metasurface scheme capable of providing dual phase control through out-of-plane plasmonic resonance of L-shape antennas. Under circularly polarized excitation at a specific wavelength, the L-shape antennas with rotating orientation angle act as spatially variant three-dimensional tilted dipoles and are able to generate desire phase delay for different polarization components. Generalized Snell's law is achieved for both in-plane and out-of-plane dipole components through arranging such L-shape antennas into arrays. These three-dimensional metasurfaces suggest a route for wavefront modulation and a variety of nanophotonic applications.
Keywords: Physics and Astronomy (miscellaneous)

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

Search Space Characterization for Approximate Logic Synthesis - Witschen, Linus Matthias; Wiersema, Tobias; Reuter, Lucas David; Platzner, Marco (2022 59th ACM/IEEE Design Automation Conference (DAC))

MUSCAT: MUS-based Circuit Approximation Technique - Witschen, Linus Matthias; Wiersema, Tobias; Artmann, Matthias; Platzner, Marco (Design, Automation and Test in Europe (DATE))

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Experimental verification of the acoustic geometric phase - Liu, Bingyi; Zhou, Zhiling; Wang, Yongtian; Zentgraf, Thomas; Li, Yong; Huang, Lingling (Applied Physics Letters)
Optical geometric phase encoded by in-plane spatial orientation of microstructures has promoted the rapid development of numerous functional meta-devices. However, pushing the concept of the geometric phase toward the acoustic community still faces challenges. In this work, we utilize two acoustic nonlocal metagratings that could support a direct conversion between an acoustic plane wave and a designated vortex mode to obtain the acoustic geometric phase, in which an orbital angular momentum conversion process plays a vital role. In addition, we realize the acoustic geometric phases of different orders by merely varying the orientation angle of the acoustic nonlocal metagratings. Intriguingly, according to our developed theory, we reveal that the reflective acoustic geometric phase, which is twice the transmissive one, can be readily realized by transferring the transmitted configuration to a reflected one. Both the theoretical study and experimental measurements verify the announced transmissive and reflective acoustic geometric phases. Moreover, the reconfigurability and continuous phase modulation that covers the 2π range shown by the acoustic geometric phases provide us with the alternatives in advanced acoustic wavefront control.
Keywords: Physics and Astronomy (miscellaneous)

Tilting nondispersive bands in an empty microcavity - Gao, Ying; Li, Yao; Ma, Xuekai; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Applied Physics Letters)
Recently, microcavities with anisotropic materials were shown to be able to create bands with non-zero local Berry curvature. The anisotropic refractive index of the cavity layer is believed to be critical in opening an energy gap at the tilted Dirac points. In this work, we show that the anticrossing between a cavity mode and a Bragg mode can also be realized within an empty microcavity without any birefringent materials in the cavity layer. Nondispersive bands are observed within the energy gap due to the particular refractive index distribution of the sample. The intrinsic TE-TM splitting and XY splitting of DBR mirrors induce the squeezing of the cavity modes in momentum space, so that the nondispersive bands are tilted and spin-dependent. Our results pave the way to investigate interesting physical phenomena of photonic modes close to or in the nondispersive bands without anisotropic cavity layers.
Keywords: Physics and Astronomy (miscellaneous)

Tilting nondispersive bands in an empty microcavity - Gao, Ying; Li, Yao; Ma, Xuekai; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

High-speed hyperspectral imaging of ferroelectric domain walls using broadband coherent anti-Stokes Raman scattering - Reitzig, Sven; Hempel, Franz; Ratzenberger, Julius; Hegarty, Peter A.; Amber, Zeeshan H.; Buschbeck, Robin; Rüsing, Michael; Eng, Lukas M. (Applied Physics Letters)
Spontaneous Raman spectroscopy (SR) is a versatile method for analysis and visualization of ferroelectric crystal structures, including domain walls. Nevertheless, the necessary acquisition time makes SR impractical for in situ analysis and large scale imaging. In this work, we introduce broadband coherent anti-Stokes Raman spectroscopy (B-CARS) as a high-speed alternative to conventional Raman techniques and demonstrate its benefits for ferroelectric domain wall analysis. Using the example of poled lithium niobate, we compare the spectral output of both techniques in terms of domain wall signatures and imaging capabilities. We extract the Raman-like resonant part of the coherent anti-Stokes signal via a Kramers–Kronig-based phase retrieval algorithm and compare the raw and phase-retrieved signals to SR characteristics. Finally, we propose a mechanism for the observed domain wall signal strength that resembles a Čerenkov-like behavior, in close analogy to domain wall signatures obtained by second-harmonic generation imaging. We, thus, lay here the foundations for future investigations on other poled ferroelectric crystals using B-CARS.
Keywords: Physics and Astronomy (miscellaneous)

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Guaranteeing Properties of Reconfigurable Hardware Circuits with Proof-Carrying Hardware - Wiersema, Tobias
Previous research in proof-carrying hardware has established the feasibility and utility of the approach, and provided a concrete solution for employing it for the certification of functional equivalence checking against a specification, but fell short in connecting it to state-of-the-art formal verification insights, methods and tools. Due to the immense complexity of modern circuits, and verification challenges such as the state explosion problem for sequential circuits, this restriction of readily-available verification solutions severely limited the applicability of the approach in wider contexts. This thesis closes the gap between the PCH approach and current advances in formal hardware verification, provides methods and tools to express and certify a wide range of circuit properties, both functional and non-functional, and presents for the first time prototypes in which circuits that are implemented on actual reconfigurable hardware are verified with PCH methods. Using these results, designers can now apply PCH to establish trust in more complex circuits, by using more diverse properties which they can express using modern, efficient property specification techniques.
Keywords: Proof-Carrying Hardware; Formal Verification; Sequential Circuits; Non-Functional Properties; Functional Properties

Timing Optimization for Virtual FPGA Configurations - Witschen, Linus Matthias; Wiersema, Tobias; Raeisi Nafchi, Masood; Bockhorn, Arne; Platzner, Marco (Proceedings of International Symposium on Applied Reconfigurable Computing (ARC'21))

Software/Hardware Co-Verification for Custom Instruction Set Processors - Jakobs, Marie-Christine; Pauck, Felix; Platzner, Marco; Wehrheim, Heike; Wiersema, Tobias (IEEE Access)
Verification of software and processor hardware usually proceeds separately, software analysis relying on the correctness of processors executing machine instructions. This assumption is valid as long as the software runs on standard CPUs that have been extensively validated and are in wide use. However, for processors exploiting custom instruction set extensions to meet performance and energy constraints the validation might be less extensive, challenging the correctness assumption. In this paper we present a novel formal approach for hardware/software co-verification targeting processors with custom instruction set extensions. We detail two different approaches for checking whether the hardware fulfills the requirements expected by the software analysis. The approaches are designed to explore a trade-off between generality of the verification and computational effort. Then, we describe the integration of software and hardware analyses for both techniques and describe a fully automated tool chain implementing the approaches. Finally, we demonstrate and compare the two approaches on example source code with custom instructions, using state-of-the-art software analysis and hardware verification techniques.
Keywords: Software Analysis; Abstract Interpretation; Custom Instruction; Hardware Verification

Optoelectronic sampling of ultrafast electric transients with single quantum dots - Widhalm, Alex; Krehs, Sebastian; Siebert, Dustin; Sharma, Nand Lal; Langer, Timo; Jonas, Björn; Reuter, Dirk; Thiede, Andreas; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
In our work, we have engineered low capacitance single quantum dot photodiodes as sensor devices for the optoelectronic sampling of ultrafast electric signals. By the Stark effect, a time-dependent electric signal is converted into a time-dependent shift of the transition energy. This shift is measured accurately by resonant ps laser spectroscopy with photocurrent detection. In our experiments, we sample the laser synchronous output pulse of an ultrafast CMOS circuit with high resolution. With our quantum dot sensor device, we were able to sample transients below 20 ps with a voltage resolution in the mV-range.
Keywords: tet_topic_qd

Malicious Routing: Circumventing Bitstream-level Verification for FPGAs - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (2021 Design, Automation & Test in Europe Conference & Exhibition (DATE))
The battle of developing hardware Trojans and corresponding countermeasures has taken adversaries towards ingenious ways of compromising hardware designs by circumventing even advanced testing and verification methods. Besides conventional methods of inserting Trojans into a design by a malicious entity, the design flow for field-programmable gate arrays (FPGAs) can also be surreptitiously compromised to assist the attacker to perform a successful malfunctioning or information leakage attack. The advanced stealthy malicious look-up-table (LUT) attack activates a Trojan only when generating the FPGA bitstream and can thus not be detected by register transfer and gate level testing and verification. However, also this attack was recently revealed by a bitstream-level proof-carrying hardware (PCH) approach. In this paper, we present a novel attack that leverages malicious routing of the inserted Trojan circuit to acquire a dormant state even in the generated and transmitted bitstream. The Trojan's payload is connected to primary inputs/outputs of the FPGA via a programmable interconnect point (PIP). The Trojan is detached from inputs/outputs during place-and-route and re-connected only when the FPGA is being programmed, thus activating the Trojan circuit without any need for a trigger logic. Since the Trojan is injected in a post-synthesis step and remains unconnected in the bitstream, the presented attack can currently neither be prevented by conventional testing and verification methods nor by recent bitstream-level verification techniques.

Proof-carrying Approximate Circuits - Witschen, Linus Matthias; Wiersema, Tobias; Platzner, Marco (IEEE Transactions On Very Large Scale Integration Systems)
Approximate circuits trade-off computational accuracy against improvements in hardware area, delay, or energy consumption. IP core vendors who wish to create such circuits need to convince consumers of the resulting approximation quality. As a solution we propose proof-carrying approximate circuits: The vendor creates an approximate IP core together with a certificate that proves the approximation quality. The proof certificate is bundled with the approximate IP core and sent off to the consumer. The consumer can formally verify the approximation quality of the IP core at a fraction of the typical computational cost for formal verification. In this paper, we first make the case for proof-carrying approximate circuits and then demonstrate the feasibility of the approach by a set of synthesis experiments using an exemplary approximation framework.
Keywords: Approximate circuit synthesis; approximate computing; error metrics; formal verification; proof-carrying hardware

Two-dimensional lateral surface superlattices in GaAs heterostructures with independent control of carrier density and modulation potential - Wang, D. Q.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R.; Klochan, O. (Applied Physics Letters)

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Search Space Characterization for AxC Synthesis - Witschen, Linus Matthias; Wiersema, Tobias; Platzner, Marco (Fifth Workshop on Approximate Computing (AxC 2020))
On the circuit level, the design paradigm Approximate Computing seeks to trade off computational accuracy against a target metric, e.g., energy consumption. This trade-off is possible for many applications due to their inherent resiliency against inaccuracies. In the past, several automated approximation frameworks have been presented, which either utilize designated approximation techniques or libraries to replace approximable circuit parts with inaccurate versions. The frameworks invoke a search algorithm to iteratively explore the search space of performance degraded circuits, and validate their quality individually. In this paper, we propose to reverse this procedure. Rather than exploring the search space, we delineate the approximate parts of the search space which are guaranteed to lead to valid approximate circuits. Our methodology is supported by formal verification and independent of approximation techniques. Eventually, the user is provided with quality bounds of the individual approximable circuit parts. Consequently, our approach guarantees that any approximate circuit which implements these parts within the determined quality constraints satisfies the global quality constraints, superseding a subsequent quality verification. In our experimental results, we present the runtimes of our approach.

Excess noise in Al x Ga 1 − xAs/GaAs based quantum rings - Riha, Christian; Buchholz, Sven S.; Chiatti, Olivio; Wieck, Andreas D.; Reuter, Dirk; Fischer, Saskia F. (Applied Physics Letters)

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Electrically controlled rapid adiabatic passage in a single quantum dot - Mukherjee, Amlan; Widhalm, Alex; Siebert, Dustin; Krehs, Sebastian; Sharma, Nandlal; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
Keywords: tet_topic_qd

Two-photon phase-sensing with single-photon detection - Vergyris, Panagiotis; Babin, Charles; Nold, Raphael; Gouzien, Elie; Herrmann, Harald; Silberhorn, Christine; Alibart, Olivier; Tanzilli, Sébastien; Kaiser, Florian (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

CIRCA: Towards a Modular and Extensible Framework for Approximate Circuit Generation - Witschen, Linus Matthias; Wiersema, Tobias; Ghasemzadeh Mohammadi, Hassan; Awais, Muhammad; Platzner, Marco (Microelectronics Reliability)
Existing approaches and tools for the generation of approximate circuits often lack generality and are restricted to certain circuit types, approximation techniques, and quality assurance methods. Moreover, only few tools are publicly available. This hinders the development and evaluation of new techniques for approximating circuits and their comparison to previous approaches. In this paper, we ﬁrst analyze and classify related approaches and then present CIRCA, our ﬂexible framework for search-based approximate circuit generation. CIRCA is developed with a focus on modularity and extensibility. We present the architecture of CIRCA with its clear separation into stages and functional blocks, report on the current prototype, and show initial experiments.
Keywords: Approximate Computing; Framework; Pareto Front; Accuracy

A Bitstream-Level Proof-Carrying Hardware Technique for Information Flow Tracking - Keerthipati, Monica
Secure hardware design is the most important aspect to be considered in addition to functional correctness. Achieving hardware security in today’s globalized Integrated Cir- cuit(IC) supply chain is a challenging task. One solution that is widely considered to help achieve secure hardware designs is Information Flow Tracking(IFT). It provides an ap- proach to verify that the systems adhere to security properties either by static verification during design phase or dynamic checking during runtime. Proof-Carrying Hardware(PCH) is an approach to verify a functional design prior to using it in hardware. It is a two-party verification approach, where the target party, the consumer requests new functionalities with pre-defined properties to the producer. In response, the producer designs the IP (Intellectual Property) cores with the requested functionalities that adhere to the consumer-defined properties. The producer provides the IP cores and a proof certificate combined into a proof-carrying bitstream to the consumer to verify it. If the verification is successful, the consumer can use the IP cores in his hardware. In essence, the consumer can only run verified IP cores. Correctly applied, PCH techniques can help consumers to defend against many unintentional modifications and malicious alterations of the modules they receive. There are numerous published examples of how to use PCH to detect any change in the functionality of a circuit, i.e., pairing a PCH approach with functional equivalence checking for combinational or sequential circuits. For non-functional properties, since opening new covert channels to leak secret information from secure circuits is a viable attack vector for hardware trojans, i.e., intentionally added malicious circuitry, IFT technique is employed to make sure that secret/untrusted information never reaches any unclassified/trusted outputs. This master thesis aims to explore the possibility of adapting Information Flow Tracking into a Proof-Carrying Hardware scenario. It aims to create a method that combines Infor- mation Flow Tracking(IFT) with a PCH approach at bitstream level enabling consumers to validate the trustworthiness of a module’s information flow without the computational costs of a complete flow analysis.

FPGA Acceleration of String Search Techniques in Huge Data Sets - Sabu, Nithin S.

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Proof-Carrying Hardware Versus the Stealthy Malicious LUT Hardware Trojan - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (Applied Reconfigurable Computing)
Reconfigurable hardware has received considerable attention as a platform that enables dynamic hardware updates and thus is able to adapt new configurations at runtime. However, due to their dynamic nature, e.g., field-programmable gate arrays (FPGA) are subject to a constant possibility of attacks, since each new configuration might be compromised. Trojans for reconfigurable hardware that evade state-of-the-art detection techniques and even formal verification, are thus a large threat to these devices. One such stealthy hardware Trojan, that is inserted and activated in two stages by compromised electronic design automation (EDA) tools, has recently been presented and shown to evade all forms of classical pre-configuration detection techniques. This paper presents a successful pre-configuration countermeasure against this ``Malicious Look-up-table (LUT)''-hardware Trojan, by employing bitstream-level Proof-Carrying Hardware (PCH). We show that the method is able to alert innocent module creators to infected EDA tools, and to prohibit malicious ones to sell infected modules to unsuspecting customers.

Efficient demultiplexed single-photon source with a quantum dot coupled to a nanophotonic waveguide - Hummel, Thomas; Ouellet-Plamondon, Claudéric; Ugur, Ela; Kulkova, Irina; Lund-Hansen, Toke; Broome, Matthew A.; Uppu, Ravitej; Lodahl, Peter (Applied Physics Letters)
Planar nanostructures allow near-ideal extraction of emission from a quantum emitter embedded within, thereby realizing deterministic single-photon sources. Such a source can be transformed into M single-photon sources by implementing active temporal-to-spatial mode demultiplexing. We report on the realization of such a demultiplexed source based on a quantum dot embedded in a nanophotonic waveguide. Efficient outcoupling (>60%) from the waveguide into a single mode optical fiber is obtained with high-efficiency grating couplers. As a proof-of-concept, active demultiplexing into M = 4 spatial channels is demonstrated by the use of electro-optic modulators with an end-to-end efficiency of >81% into single-mode fibers. Overall, we demonstrate four-photon coincidence rates of >1 Hz even under nonresonant excitation of the quantum dot. The main limitation of the current source is the residual population of other exciton transitions, which corresponds to a finite preparation efficiency of the desired transition. We quantitatively extract a preparation efficiency of 15% using the second-order correlation function measurements. The experiment highlights the applicability of planar nanostructures as efficient multiphoton sources through temporal-to-spatial demultiplexing and lays out a clear path way of how to scale up toward demonstrating quantum advantages with the quantum dot sources.

CIRCA: Towards a Modular and Extensible Framework for Approximate Circuit Generation - Witschen, Linus Matthias; Wiersema, Tobias; Ghasemzadeh Mohammadi, Hassan; Awais, Muhammad; Platzner, Marco (Third Workshop on Approximate Computing (AxC 2018))
Existing approaches and tools for the generation of approximate circuits often lack generality and are restricted to certain circuit types, approximation techniques, and quality assurance methods. Moreover, only few tools are publicly available. This hinders the development and evaluation of new techniques for approximating circuits and their comparison to previous approaches. In this paper, we ﬁrst analyze and classify related approaches and then present CIRCA, our ﬂexible framework for search-based approximate circuit generation. CIRCA is developed with a focus on modularity and extensibility. We present the architecture of CIRCA with its clear separation into stages and functional blocks, report on the current prototype, and show initial experiments.
Keywords: Approximate Computing; Framework; Pareto Front; Accuracy

Making the Case for Proof-carrying Approximate Circuits - Witschen, Linus Matthias; Wiersema, Tobias; Platzner, Marco (4th Workshop On Approximate Computing (WAPCO 2018))

Enforcing IP Core Connection Properties with Verifiable Security Monitors - Jentzsch, Felix Paul
Keywords: Approximate Computing; Proof-Carrying Hardware; Formal Veriﬁcation

Streak camera imaging of single photons at telecom wavelength - Allgaier, Markus; Ansari, Vahid; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Donohue, John Matthew; Czerniuk, Thomas; Aßmann, Marc; Bayer, Manfred; Brecht, Benjamin; Silberhorn, Christine (Applied Physics Letters)

A Framework for the Synthesis of Approximate Circuits - Witschen, Linus Matthias

Noble metal free photocatalytic H2 generation on black TiO2: On the influence of crystal facets vs. crystal damage - Liu, Ning; Steinrück, Hans-Georg; Osvet, Andres; Yang, Yuyun; Schmuki, Patrik (Applied Physics Letters)

Proof-Carrying Hardware via Inductive Invariants - Isenberg, Tobias; Platzner, Marco; Wehrheim, Heike; Wiersema, Tobias (ACM Transactions on Design Automation of Electronic Systems)
Proof-carrying hardware (PCH) is a principle for achieving safety for dynamically reconfigurable hardware systems. The producer of a hardware module spends huge effort when creating a proof for a safety policy. The proof is then transferred as a certificate together with the configuration bitstream to the consumer of the hardware module, who can quickly verify the given proof. Previous work utilized SAT solvers and resolution traces to set up a PCH technology and corresponding tool flows. In this article, we present a novel technology for PCH based on inductive invariants. For sequential circuits, our approach is fundamentally stronger than the previous SAT-based one since we avoid the limitations of bounded unrolling. We contrast our technology to existing ones and show that it fits into previously proposed tool flows. We conduct experiments with four categories of benchmark circuits and report consumer and producer runtime and peak memory consumption, as well as the size of the certificates and the distribution of the workload between producer and consumer. Experiments clearly show that our new induction-based technology is superior for sequential circuits, whereas the previous SAT-based technology is the better choice for combinational circuits.

Controlling the optical spin Hall effect with light - Lafont, O.; Luk, S. M. H.; Lewandowski, P.; Kwong, N. H.; Leung, P. T.; Galopin, E.; Lemaitre, A.; Tignon, J.; Schumacher, Stefan; Baudin, E.; Binder, R. (Applied Physics Letters)

Species transport on the target during high power impulse magnetron sputtering - Layes, V.; Monje, S.; Corbella, C.; Trieschmann, J.; de los Arcos de Pedro, Maria Teresa; von Keudell, A. (Applied Physics Letters)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

An Architecture and Design Tool Flow for Embedding a Virtual FPGA into a Reconfigurable System-on-Chip - Wiersema, Tobias; Bockhorn, Arne; Platzner, Marco (Computers & Electrical Engineering)
Virtual field programmable gate arrays (FPGA) are overlay architectures realized on top of physical FPGAs. They are proposed to enhance or abstract away from the physical FPGA for experimenting with novel architectures and design tool flows. In this paper, we present an embedding of a ZUMA-based virtual FPGA fabric into a complete configurable system-on-chip. Such an embedding is required to fully harness the potential of virtual FPGAs, in particular to give the virtual circuits access to main memory and operating system services, and to enable a concurrent operation of virtualized and non-virtualized circuitry. We discuss our extension to ZUMA and its embedding into the ReconOS operating system for hardware/software systems. Furthermore, we present an open source tool flow to synthesize configurations for the virtual FPGA, along with an analysis of the area and delay overheads involved.

Verifying Worst-Case Completion Times for Reconfigurable Hardware Modules using Proof-Carrying Hardware - Wiersema, Tobias; Platzner, Marco (Proceedings of the 11th International Symposium on Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC 2016))
Runtime reconfiguration can be used to replace hardware modules in the field and even to continuously improve them during operation. Runtime reconfiguration poses new challenges for validation, since the required properties of newly arriving modules may be difficult to check fast enough to sustain the intended system dynamics. In this paper we present a method for just-in-time verification of the worst-case completion time of a reconfigurable hardware module. We assume so-called run-to-completion modules that exhibit start and done signals indicating the start and end of execution, respectively. We present a formal verification approach that exploits the concept of proof-carrying hardware. The approach tasks the creator of a hardware module with constructing a proof of the worst-case completion time, which can then easily be checked by the user of the module, just prior to reconfiguration. After explaining the verification approach and a corresponding tool flow, we present results from two case studies, a short term synthesis filter and a multihead weigher. The resultsclearly show that cost of verifying the completion time of the module is paid by the creator instead of the user of the module.

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Periodic domain inversion in x-cut single-crystal lithium niobate thin film - Mackwitz, P.; Rüsing, Michael; Berth, Gerhard; Widhalm, A.; Müller, K.; Zrenner, Artur (Applied Physics Letters)
We report the fabrication of periodically poled domain patterns in x-cut lithium niobate thin-film. Here, thin films on insulator have drawn particular attention due to their intrinsic waveguiding properties offering high mode confinement and smaller devices compared to in-diffused waveguides in bulk material. In contrast to z-cut thin film lithium niobate, the x-cut geometry does not require back electrodes for poling. Further, the x-cut geometry grants direct access to the largest nonlinear and electro-optical tensor element, which overall promises smaller devices. The domain inversion was realized via electric field poling utilizing deposited aluminum top electrodes on a stack of LN thin film/SiO2 layer/Bulk LN, which were patterned by optical lithography. The periodic domain inversion was verified by non-invasive confocal second harmonic microscopy. Our results show domain patterns in accordance to the electrode mask layout. The second harmonic signatures can be interpreted in terms of spatially, overlapping domain filaments which start their growth on the þz side.

On-The-Fly Verification of Reconfigurable Image Processing Modules based on a Proof-Carrying Hardware Approach - Wiersema, Tobias; Wu, Sen; Platzner, Marco (Proceedings of the International Symposium in Reconfigurable Computing (ARC))
Proof-carrying hardware is an approach that has recently been proposed for the efficient verification of reconfigurable modules. We present an application of proof-carrying hardware to guarantee the correct functionality of dynamically reconfigured image processing modules. Our prototype comprises a reconfigurable-system-on-chip with an embedded virtual FPGA fabric. This setup allows us to leverage open source FPGA synthesis and backend tools to produce FPGA configuration bitstreams with an open format and, thus, to demonstrate and experimentally evaluate proof-carrying hardware at the bitstream level.

Ultrafast carrier dynamics and resonant inter-miniband nonlinearity of a cubic GaN/AlN superlattice - Jostmeier, Thorben; Wecker, Tobias; Reuter, Dirk; As, Donat Josef; Betz, Markus (Applied Physics Letters)

Fabrication and characterisation of gallium arsenide ambipolar quantum point contacts - Chen, J. C. H.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Trunov, K.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Photonic crystal cavities with metallic Schottky contacts - Quiring, W.; Al-Hmoud, M.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Applied Physics Letters)
We report about the fabrication and analysis of high Q photonic crystal cavities with metallic Schottky-contacts. The structures are based on GaAs n-i membranes with an InGaAs quantum well in the i-region and nanostructured low ohmic metal top-gates. They are designed for photocurrent readout within the cavity and fast electric manipulations. The cavity structures are characterized by photoluminescence and photocurrent spectroscopy under resonant excitation. We find strong cavity resonances in the photocurrent spectra and surprisingly high Q-factors up to 6500. Temperature dependent photocurrent measurements in the region between 4.5K and 310K show an exponential enhancement of the photocurrent signal and an external quantum efficiency up to 0.26.

Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.

Konzept und Implementation einer Benutzeroberfläche zur Generierung virtueller FPGAs - Meißner, Roland

Electrically tunable zero dispersion wavelengths in photonic crystal fibers filled with a dual frequency addressable liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Confocal shift interferometry of coherent emission from trapped dipolar excitons - Repp, J.; Schinner, G. J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Wurstbauer, U.; Kotthaus, J. P.; Holleitner, A. W. (Applied Physics Letters)

Memory Security in Reconfigurable Computers: Combining Formal Verification with Monitoring - Wiersema, Tobias; Drzevitzky, Stephanie; Platzner, Marco (Proceedings of the International Conference on Field-Programmable Technology (FPT))
Ensuring memory access security is a challenge for reconfigurable systems with multiple cores. Previous work introduced access monitors attached to the memory subsystem to ensure that the cores adhere to pre-defined protocols when accessing memory. In this paper, we combine access monitors with a formal runtime verification technique known as proof-carrying hardware to guarantee memory security. We extend previous work on proof-carrying hardware by covering sequential circuits and demonstrate our approach with a prototype leveraging ReconOS/Zynq with an embedded ZUMA virtual FPGA overlay. Experiments show the feasibility of the approach and the capabilities of the prototype, which constitutes the first realization of proof-carrying hardware on real FPGAs. The area overheads for the virtual FPGA are measured as 2x-10x, depending on the resource type. The delay overhead is substantial with almost 100x, but this is an extremely pessimistic estimate that will be lowered once accurate timing analysis for FPGA overlays become available. Finally, reconfiguration time for the virtual FPGA is about one order of magnitude lower than for the native Zynq fabric.

Integrating Software and Hardware Verification - Jakobs, Marie-Christine; Platzner, Marco; Wiersema, Tobias; Wehrheim, Heike (Proceedings of the 11th International Conference on Integrated Formal Methods (iFM))
Verification of hardware and software usually proceeds separately, software analysis relying on the correctness of processors executing instructions. This assumption is valid as long as the software runs on standard CPUs that have been extensively validated and are in wide use. However, for processors exploiting custom instruction set extensions to meet performance and energy constraints the validation might be less extensive, challenging the correctness assumption.In this paper we present an approach for integrating software analyses with hardware verification, specifically targeting custom instruction set extensions. We propose three different techniques for deriving the properties to be proven for the hardware implementation of a custom instruction in order to support software analyses. The techniques are designed to explore the trade-off between generality and efficiency and span from proving functional equivalence over checking the rules of a particular analysis domain to verifying actual pre and post conditions resulting from program analysis. We demonstrate and compare the three techniques on example programs with custom instructions, using stateof-the-art software and hardware verification techniques.

Embedding FPGA Overlays into Configurable Systems-on-Chip: ReconOS meets ZUMA - Wiersema, Tobias; Bockhorn, Arne; Platzner, Marco (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Virtual FPGAs are overlay architectures realized on top of physical FPGAs. They are proposed to enhance or abstract away from the physical FPGA for experimenting with novel architectures and design tool flows. In this paper, we present an embedding of a ZUMA-based virtual FPGA fabric into a complete configurable system-on-chip. Such an embedding is required to fully harness the potential of virtual FPGAs, in particular to give the virtual circuits access to main memory and operating system services, and to enable a concurrent operation of virtualized and non-virtualized circuitry. We discuss our extension to ZUMA and its embedding into the ReconOS operating system for hardware/software systems. Furthermore, we present an open source tool flow to synthesize configurations for the virtual FPGA.

Magneto-optical studies of Gd-implanted GaN: No spin alignment of conduction band electrons - Buß, J. H.; Rudolph, J.; Shvarkov, S.; Semond, F.; Reuter, Dirk; Wieck, A. D.; Hägele, D. (Applied Physics Letters)

Whispering gallery modes in zinc-blende AlN microdisks containing non-polar GaN quantum dots - Bürger, M.; Ruth, M.; Declair, S.; Förstner, Jens; Meier, Cedrik; As, Donat Josef (Applied Physics Letters)
Whispering gallery modes (WGMs) were observed in 60 nm thin cubic AlN microdisk resonators containing a single layer of non-polar cubic GaN quantum dots. Freestanding microdisks were patterned by means of electron beam lithography and a two step reactive ion etching process. Micro-photoluminescence spectroscopy investigations were performed for optical characterization. We analyzed the mode spacing for disk diameters ranging from 2-4 lm. Numerical investigations using three dimensional finite difference time domain calculations were in good agreement with the experimental data. Whispering gallery modes of the radial orders 1 and 2 were identified by means of simulated mode field distributions.
Keywords: tet_topic_qd; tet_topic_microdisk

Microresonator-enhanced electroluminescence of an organic light emitting diode based on a columnar liquid crystal - Vollbrecht, Joachim; Kasdorf, Olga; Quiring, Viktor; Suche, Hubertus; Bock, Harald; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

A double-threshold technique for fast time-correspondence imaging - Li, Ming-Fei; Zhang, Yu-Ran; Liu, Xue-Feng; Yao, Xu-Ri; Luo, Kai Hong; Fan, Heng; Wu, Ling-An (Applied Physics Letters)

Magnetic field dependence of the spin relaxation length in spin light-emitting diodes - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Applied Physics Letters)

Momentum matching in the tunneling between 2-dimensional and 0-dimensional electron systems - Beckel, Andreas; Zhou, Daming; Marquardt, Bastian; Reuter, Dirk; Wieck, Andreas D.; Geller, Martin; Lorke, Axel (Applied Physics Letters)

Non-resonant optical excitation of mode-locked electron spin coherence in (In,Ga)As/GaAs quantum dot ensemble - Schwan, A.; Varwig, S.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Applied Physics Letters)

Electron-nuclei spin coupling in GaAs—Free versus localized electrons - Huang, J.; Chen, Y. S.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Applied Physics Letters)

Fabrication and characterization of ambipolar devices on an undoped AlGaAs/GaAs heterostructure - Chen, J. C. H.; Wang, D. Q.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Carrier localization in ZnO quantum wires - Kröger, Philipp; Ruth, Marcel; Weber, Nils; Meier, Cedrik (Applied Physics Letters)

High power impulse magnetron sputtering discharges: Instabilities and plasma self-organization - Ehiasarian, A. P.; Hecimovic, A.; de los Arcos de Pedro, Maria Teresa; New, R.; Schulz-von der Gathen, V.; Böke, M.; Winter, J. (Applied Physics Letters)

Switching performance of a polymer-stabilized antiferroelectric liquid crystal based on bent-core molecules - Atorf, B.; Hoischen, A.; Ros, M. B.; Gimeno, N.; Tschierske, C.; Dantlgraber, G.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Electrical fine tuning of liquid crystal lasers - Schmidtke, Jürgen; Jünnemann, Gisela; Keuker-Baumann, Susanne; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Programming and Scheduling Model for Supporting Heterogeneous Accelerators in Linux - Beisel, Tobias; Wiersema, Tobias; Plessl, Christian; Brinkmann, André (Proc. Workshop on Computer Architecture and Operating System Co-design (CAOS))
Keywords: funding-enhance

The influence of charged InAs quantum dots on the conductance of a two-dimensional electron gas: Mobility vs. carrier concentration - Marquardt, B.; Beckel, A.; Lorke, A.; Wieck, A. D.; Reuter, Dirk; Geller, M. (Applied Physics Letters)

Mode-filtered electron injection into a waveguide interferometer - Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (Applied Physics Letters)

Optically detected nuclear magnetic resonance in n-GaAs using an on-chip microcoil - Chen, Y. S.; Huang, J.; Reuter, Dirk; Ludwig, A.; Wieck, A. D.; Bacher, G. (Applied Physics Letters)

Room temperature spin relaxation length in spin light-emitting diodes - Soldat, Henning; Li, Mingyuan; Gerhardt, Nils C.; Hofmann, Martin R.; Ludwig, Arne; Ebbing, Astrid; Reuter, Dirk; Wieck, Andreas D.; Stromberg, Frank; Keune, Werner; Wende, Heiko (Applied Physics Letters)

Efficient electro-optic switching in a photonic liquid crystal fiber - Lorenz, Alexander; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Cooperative multitasking for heterogeneous accelerators in the Linux Completely Fair Scheduler - Beisel, Tobias; Wiersema, Tobias; Plessl, Christian; Brinkmann, André (Proc. Int. Conf. on Application-Specific Systems, Architectures, and Processors (ASAP))

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Nanostructures in p-GaAs with improved tunability - Csontos, M.; Komijani, Y.; Shorubalko, I.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Full-wave rectification based upon hot-electron thermopower - Wiemann, M.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, A.; Meier, C. (Applied Physics Letters)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Meier, Cedrik (Applied Physics Letters)
We have integrated individual (In,Ga)As quantum dots (QDs) using site-controlled molecular beam epitaxial growth into the intrinsic region of a p-i-n junction diode. This is achieved using an in situ combination of focused ion beam prepatterning, annealing, and overgrowth, resulting in arrays of individually electrically addressable (In,Ga)As QDs with full control on the lateral position. Using microelectroluminescence spectroscopy we demonstrate that these QDs have the same optical quality as optically pumped Stranski–Krastanov QDs with random nucleation located in proximity to a doped interface. The results suggest that this technique is scalable and highly interesting for different applications in quantum devices.

Nonpolar cubic AlGaN/GaN heterojunction field-effect transistor on Ar+ implanted 3C–SiC (001) - Tschumak, E.; Granzner, R.; Lindner, Jörg; Schwierz, F.; Lischka, K.; Nagasawa, H.; Abe, M.; As, Donald (Applied Physics Letters)
A heterojunction field-effect transistor (HFET) was fabricated of nonpolar cubic AlGaN/GaN grown on Ar+ implanted 3C–SiC (001) by molecular beam epitaxy. The device shows a clear field effect at positive bias voltages with V_th=0.6 V. The HFET output characteristics were calculated using ATLAS simulation program. The electron channel at the cubic AlGaN/GaN interface was detected by room temperature capacitance-voltage measurements.

Scheduling Support for Heterogeneous Hardware Accelerators under Linux - Wiersema, Tobias

Measurement of effective electron mass in biaxial tensile strained silicon on insulator - Feste, Sebastian F.; Schäpers, Thomas; Buca, Dan; Zhao, Qing Tai; Knoch, Joachim; Bouhassoune, Mohammed; Schindlmayr, Arno; Mantl, Siegfried (Applied Physics Letters)
We present measurements of the effective electron mass in biaxial tensile strained silicon on insulator (SSOI) material with 1.2 GPa stress and in unstrained SOI. Hall-bar metal oxide semiconductor field effect transistors on 60 nm SSOI and SOI were fabricated and Shubnikov–de Haas oscillations in the temperature range of T=0.4–4 K for magnetic fields of B=0–10 T were measured. The effective electron mass in SSOI and SOI samples was determined as mt=(0.20±0.01)m0. This result is in excellent agreement with first-principles calculations of the effective electron mass in the presence of strain.

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Ellipsoidal InAs quantum dots observed by cross-sectional scanning tunneling microscopy - Blokland, J. H.; Bozkurt, M.; Ulloa, J. M.; Reuter, Dirk; Wieck, A. D.; Koenraad, P. M.; Christianen, P. C. M.; Maan, J. C. (Applied Physics Letters)

Using a two-dimensional electron gas to study nonequilibrium tunneling dynamics and charge storage in self-assembled quantum dots - Marquardt, B.; Geller, M.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Probing the band structure of InAs∕GaAs quantum dots by capacitance-voltage and photoluminescence spectroscopy - Lei, W.; Offer, M.; Lorke, A.; Notthoff, C.; Meier, Cedrik; Wibbelhoff, O.; Wieck, A. D. (Applied Physics Letters)

Magnetotransport in Gd-implanted wurtzite GaN∕AlxGa1−xN high electron mobility transistor structures - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Cordier, Y.; Wieck, A. D. (Applied Physics Letters)

Coherent spin dynamics in Permalloy-GaAs hybrids at room temperature - Hohage, P. E.; Nannen, J.; Halm, S.; Bacher, G.; Wahle, M.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electrical detection of photoinduced spins both at room temperature and in remanence - Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W.; Wende, H.; Petracic, O.; Westerholt, K. (Applied Physics Letters)